The Principal Navigations, Voyages, Traffiques and Discoveries of the English Nation $1 (BVolume 02s - Hakluyt, Richard, 1552?-1616 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Principal Navigations, Voyages, Traffiques and Discoveries of the English Nation" by Richard Hakluyt is a historical account likely composed in the late 16th century. This work serves as a comprehensive anthology documenting the maritime explorations conducted by English navigators, traders, and adventurers during this period, focusing particularly on their encounters with various foreign nations, cultures, and terrains. The opening of this extensive volume presents detailed accounts of the English endeavors in far-flung territories, particularly their interactions with the Tartars and the Eastern European landscape. Through narratives spanning from the confessions of an Englishman captured by Tartars to descriptions of their customs and warfare, it sets the stage for Hakluyt's exploration of the socio-political complexities and cultural exchanges that characterized these adventures. The text emphasizes the harsh realities faced by those in contact with the Tartars, illustrating themes of violence, survival, and the quest for dominance in foreign lands. (This is an automatically generated summary.)
Release date is 2005-02-01
Produced by Karl Hagen, Juliet Sutherland, and the Online Distributed Proofreading team
Keywords: Voyages and travels; Discoveries in geography -- English